Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Tracing the sources of noble gases for helium prospectivity in the Western Canada Sedimentary Basin - Stuart M.V. Gilfillan; Emma Martin-Roberts; Nicholas Utting; Rachel Utley; Kirk Osadetz; Don Lawton (Chemical Geology, 2026)

The geochemical and isotopic composition of the Miocene Vestfirðir basalts, Northwest Iceland: Tracking the evolution of the Iceland mantle plume - Ugur Balci; Emma Martin-Roberts; Björn Hardarson; J. Godfrey Fitton; Valerie Olive; Ryan Ickert; Darren F. Mark; Finlay M. Stuart (Chemical Geology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Changing volatile emissions and sources along the Ethiopian Rift - Abate A. Melaku; Gemechu B. Teferi; Takele Mihretie; Snorri Gudbrandsson; Yared Sinetebeb; Peter H. Barry; Tobias P. Fischer; Finlay M. Stuart; Ugur Balci; Sæmundur A. Halldórsson; Chris J. Ballentine; Darren J. Hillegonds; et al. (Earth and Planetary Science Letters, 2026)

Enhanced hydrogeochemical baseline of a CO2 injection facility in southern Alberta, Canada - Nicholas Utting; Kirk G. Osadetz; Bernhard Mayer; Tiago Morais; Stuart M.V. Gilfillan; Michael Nightingale; Thomas Darrah; Emma Martin-Roberts; Don Lawton (International Journal of Greenhouse Gas Control, 2026)

Impact of wildfires on sediment quality in estuaries in New South Wales, Australia - Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Mark Farrell; Sally A. Bracewell; Emma L. Johnston (Chemosphere, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

The influence of subtidal Laminaria canopies on local environmental conditions and the structure of understorey communities - Emma Stuart; Nathan King; Dan Smale (Marine Environmental Research, 2025)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Rapid remote volcanic ashfall impact assessment for the 2022 eruption of Hunga volcano, Tonga: a bespoke approach and lessons identified - Alana M. Weir; James H. Williams; Thomas M. Wilson; Josh L. Hayes; Carol Stewart; Graham S. Leonard; Christina Magill; Susanna F. Jenkins; Shaun Williams; Heather M. Craig; Taaniela Kula; Stuart Fraser; et al. (Bulletin of Volcanology, 2024)
When disasters occur, rapid impact assessments are required to prioritise response actions, support in-country efforts and inform the mobilisation of aid. The 15 January 2022 eruption of Hunga volcano, Tonga, and the resulting atmospheric shockwave, ashfall, underwater mass disturbance and tsunami, caused substantial impacts across the Kingdom of Tonga. Volcanic impacts on the scale observed after the eruption are rare, necessitating a reliance on international advice and assistance. The situation was complicated by the loss of Tonga’s international submarine fibreoptic cable (causing a complete loss of communications for approximately 20 days) along with border closures due to the COVID-19 pandemic. A need emerged for a rapid remote volcanic impact assessment and provision of specialist advice to help inform the response of international partners. Here we present a novel methodology for conducting rapid remote volcanic ashfall impact assessments, conducted over a 10-day period following the eruption. We used three different hazard models for ashfall thickness across the main island of Tongatapu and available asset information and vulnerability functions for buildings, agriculture, electricity networks, water supply and roads, to provide initial estimates of losses due to ashfall from the 15 January eruption. For buildings, we estimated losses both as total losses and as percentages of the total replacement cost of buildings on Tongatapu. For agriculture, we made probabilistic estimates of production losses for three different crop classes. For ashfall clean-up, we estimated ranges of ashfall volumes requiring clean-up from road surfaces and roofs. For water supply, electricity networks and roads, our analysis was limited to assessing the exposure of important assets to ashfall, as we had insufficient information on system configurations to take the analysis further. Key constraints on our analysis were the limited nature of critical infrastructure asset inventories and the lack of volcanic vulnerability models for tropical regions including Pacific Island nations. Key steps towards iteratively improving rapid remote impact assessments will include developing vulnerability functions for tropical environments as well as ground-truthing estimated losses from remote approaches against in-person impact assessment campaigns.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Progress on improving animal welfare and experiment translatability using an animal model of venom induced consumption coagulopathy - Amy E. Marriott; Emma Stars; Nicholas Casewell; Stuart Ainsworth (Toxicon, 2024)

Biogeochemical plumbing of pioneer mangrove intertidal flats in French Guiana - Robert Aller; Issac Klingensmith; Thomas Stieglitz; Christina Heilbrun; Stuart Waugh; Adelaide Aschenbroich; Gerard Thouzeau; Emma Michaud (Regional Environmental Change, 2024)
Migrating mudbanks are characteristic features of the vast Amazon-Guianas coastline along Northeastern South America. As illustrated by sites in French Guiana, consolidating mudflats that periodically transition to mangrove forest are permeated by extensive crustacean burrow systems, sometimes in isolation but more often in close association with morpho-sedimentary structures such as tidal pools and channels. Burrow structures are critical to mangrove growth. In this study, we evaluated the ways in which burrows act as complex conduits that plumb deposits for solute exchange with overlying water. We sampled burrows during low tide when irrigation is inhibited and burrow water rapidly becomes anoxic. The products of diagenetic reactions, for example: NH 4 + , N 2 , and Si(OH) 4 , build up with time, revealing sedimentary reaction rates and fluxes. When oxygenated, burrow walls are zones of intense coupled redox reactions such as nitrification-denitrification. Build-up often is lower in burrows connected directly to tidal pools where photosynthetic activity consumes remineralized nutrients, and burrows can remain periodically irrigated at low tide. During flood, burrows, particularly those that connect tidal pools laterally to channels, can be rapidly flushed and oxygenated as channel water rises and then spreads across flats. Burrow flushing produces enhanced concentrations of nutrients within the leading edge of the flood as seawater moves progressively towards and into adjacent mangroves. Estimates of burrow volumes obtained from drone surveys together with burrow solute production rates allow upscaling of burrow-sourced metabolite fluxes; however, these are extremely variable due to variable burrow geometries, connections between burrows, pools, and channels, and burrow water residence times (oxygenation). The flushing of burrows during flood results in a rectification of sediment-water fluxes shoreward and enhances the delivery of nutrients from the flats into adjacent mangroves and pools, presumably stimulating colonization and forest growth.

Aligning theoretical and empirical representations of soil carbon-to-nitrogen stoichiometry with process-based terrestrial biogeochemistry models - Katherine S. Rocci; Cory C. Cleveland; Brooke A. Eastman; Katerina Georgiou; A. Stuart Grandy; Melannie D. Hartman; Emma Hauser; Hannah Holland-Moritz; Emily Kyker-Snowman; Derek Pierson; Peter B. Reich; Else P. Schlerman; et al. (Soil Biology and Biochemistry, 2024)

Association between ambient temperature and common allergenic pollen and fungal spores: A 52-year analysis in central England, United Kingdom - Holly C.Y. Lam; Samuel Anees-Hill; Jack Satchwell; Fiona Symon; Helen Macintyre; Catherine H. Pashley; Emma L. Marczylo; Philippa Douglas; Stuart Aldridge; Anna Hansell (Science of The Total Environment, 2024)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Assessing animal welfare during a stranding of pygmy killer whales ( Feresa attenuata ) - Rebecca M. Boys; Ngaio J. Beausoleil; Stuart Hunter; Emma L. Betty; Bethany Hinton; Karen A. Stockin (Marine Mammal Science, 2023)
Empirical assessment of cetacean welfare to inform stranding interventions is lacking. Here, potential welfare indicators are described for two stranded pygmy killer whales ( Feresa attenuata ), along with euthanasia procedures and pathology of potential relevance. The animals were filmed for 3.5 and 1.5 hr, respectively, allowing assessment of 19 indicators, including animal behaviors and human interventions. Eight interventions and 19 animal behaviors were identified; 17 and 11 behaviors were displayed by animal 1 and 2, respectively. Examination of ballistics euthanasia revealed atypical projectile placement and characterized animal behavioral responses, but welfare implications could not be assessed as insensibility was not verified in‐field. Pulmonary edema and renal degeneration were documented in both animals; differential etiologies include ischemia–reperfusion, shock, and/or myopathy. Potential relationships among histopathology and welfare indicators are explored to infer affective experiences. For example, simultaneous head‐lifting with respiration increased over time which, alongside pulmonary edema, suggests these animals experienced breathlessness. Other likely affective states include fatigue and discomfort; there are insufficient data to estimate the intensity or duration of these experiences or to provide an overall welfare grade/score. Further data are required to validate the proposed welfare indicators and to progress development of holistic approaches to welfare assessment at cetacean strandings.

Understanding the effect of metamictization on the efficiency of zircon milling - Matthew J. Smith; Emma Jones; Stuart Blackburn; Richard W. Greenwood (Minerals Engineering, 2023)

Contaminant pulse following wildfire is associated with shifts in estuarine benthic communities - Sally A. Bracewell; Thayanne L. Barros; Mariana Mayer-Pinto; Katherine A. Dafforn; Stuart L. Simpson; Emma L. Johnston (Environmental Pollution, 2023)

Factors controlling the effects of mutualistic bacteria on plants associated with fungi - Daniel A. Bastías; Emma R. Applegate; Linda J. Johnson; Stuart D. Card (Ecology Letters, 2022)
Plants interacting with mutualistic fungi (MF) or antagonistic fungi (AF) can form associations with bacteria. We assessed whether the performance gain conferred by mutualistic bacteria to fungal‐associated plants is affected by the interaction between symbiont traits, type of bacterial‐protective traits against AF and abiotic/biotic stresses. Results showed that (A) performance gain conferred by bacteria to MF‐associated plants was greater when symbionts promoted distinct rather than similar plant functions, (B) bacterial‐based alleviation of the AF's negative effect on plants was independent of the type of protective trait, (C) bacteria promoted a greater performance of symbiotic plants in presence of biotic, but not abiotic, stress compared to stress‐free situations. The plant performance gain was not affected by any fungal‐bacterial trait combination but optimised when bacteria conferred resistance traits in biotic stress situations. The effects of bacteria on fungal‐associated plants were controlled by the interaction between the symbionts' functional traits and the relationship between bacterial traits and abiotic/biotic stresses.

Limited Progress in Improving Gender and Geographic Representation in Coral Reef Science - Gabby N. Ahmadia; Samantha H. Cheng; Dominic A. Andradi-Brown; Stacy K. Baez; Megan D. Barnes; Nathan J. Bennett; Stuart J. Campbell; Emily S. Darling; Estradivari; David Gill; Erika Gress; Georgina G. Gurney; et al. (Frontiers in Marine Science, 2021)
Despite increasing recognition of the need for more diverse and equitable representation in the sciences, it is unclear whether measurable progress has been made. Here, we examine trends in authorship in coral reef science from 1,677 articles published over the past 16 years (2003–2018) and find that while representation of authors that are women (from 18 to 33%) and from non-OECD nations (from 4 to 13%) have increased over time, progress is slow in achieving more equitable representation. For example, at the current rate, it would take over two decades for female representation to reach 50%. Given that there are more coral reef non-OECD countries, at the current rate, truly equitable representation of non-OECD countries would take even longer. OECD nations also continue to dominate authorship contributions in coral reef science (89%), in research conducted in both OECD (63%) and non-OECD nations (68%). We identify systemic issues that remain prevalent in coral reef science (i.e., parachute science, gender bias) that likely contribute to observed trends. We provide recommendations to address systemic biases in research to foster a more inclusive global science community. Adoption of these recommendations will lead to more creative, innovative, and impactful scientific approaches urgently needed for coral reefs and contribute to environmental justice efforts.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Workflow for the Generation of Expert-Derived Training and Validation Data: A View to Global Scale Habitat Mapping - Chris M. Roelfsema; Mitchell Lyons; Nicholas Murray; Eva M. Kovacs; Emma Kennedy; Kathryn Markey; Rodney Borrego-Acevedo; Alexandra Ordoñez Alvarez; Chantel Say; Paul Tudman; Meredith Roe; Jeremy Wolff; et al. (Frontiers in Marine Science, 2021)
Our ability to completely and repeatedly map natural environments at a global scale have increased significantly over the past decade. These advances are from delivery of a range of on-line global satellite image archives and global-scale processing capabilities, along with improved spatial and temporal resolution satellite imagery. The ability to accurately train and validate these global scale-mapping programs from what we will call “reference data sets” is challenging due to a lack of coordinated financial and personnel resourcing, and standardized methods to collate reference datasets at global spatial extents. Here, we present an expert-driven approach for generating training and validation data on a global scale, with the view to mapping the world’s coral reefs. Global reefs were first stratified into approximate biogeographic regions, then per region reference data sets were compiled that include existing point data or maps at various levels of accuracy. These reference data sets were compiled from new field surveys, literature review of published surveys, and from individually sourced contributions from the coral reef monitoring and management agencies. Reference data were overlaid on high spatial resolution satellite image mosaics (3.7 m × 3.7 m pixels; Planet Dove) for each region. Additionally, thirty to forty satellite image tiles; 20 km × 20 km) were selected for which reference data and/or expert knowledge was available and which covered a representative range of habitats. The satellite image tiles were segmented into interpretable groups of pixels which were manually labeled with a mapping category via expert interpretation. The labeled segments were used to generate points to train the mapping models, and to validate or assess accuracy. The workflow for desktop reference data creation that we present expands and up-scales traditional approaches of expert-driven interpretation for both manual habitat mapping and map training/validation. We apply the reference data creation methods in the context of global coral reef mapping, though our approach is broadly applicable to any environment. Transparent processes for training and validation are critical for usability as big data provide more opportunities for managers and scientists to use global mapping products for science and conservation of vulnerable and rapidly changing ecosystems.

A global coral reef probability map generated using convolutional neural networks - Jiwei Li; David E. Knapp; Nicholas S. Fabina; Emma V. Kennedy; Kirk Larsen; Mitchell B. Lyons; Nicholas J. Murray; Stuart R. Phinn; Chris M. Roelfsema; Gregory P. Asner (Coral Reefs, 2020)

Habitat maps to enhance monitoring and management of the Great Barrier Reef - Chris M. Roelfsema; Eva M. Kovacs; Juan Carlos Ortiz; David P. Callaghan; Karlo Hock; Mathieu Mongin; Kasper Johansen; Peter J. Mumby; Magnus Wettle; Mike Ronan; Petra Lundgren; Emma V. Kennedy; et al. (Coral Reefs, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Autonomous adaptation to climate-driven change in marine biodiversity in a global marine hotspot - Gretta T. Pecl; Emily Ogier; Sarah Jennings; Ingrid van Putten; Christine Crawford; Hannah Fogarty; Stewart Frusher; Alistair J. Hobday; John Keane; Emma Lee; Catriona MacLeod; Craig Mundy; et al. (Ambio, 2019)

Incorporating social dimensions in planning, managing and evaluating environmental projects - C. Louise Goggin; Thomas Barrett; John Leys; Gregory Summerell; Emma Gorrod; Stuart Waters; Mark Littleboy; Tony D. Auld; Michael J. Drielsma; Brian R. Jenkins (Environmental Management, 2019)

Long‐term research reveals multiple relationships between the abundance and impacts of a non‐native species - David L. Strayer; Christopher T. Solomon; Stuart E. G. Findlay; Emma J. Rosi (Limnology and Oceanography, 2019)
Non‐native species are among the most important drivers of the structure and function of modern ecosystems. The ecological impacts of a non‐native species ought to depend on the size and characteristics of its population, but the exact nature of this population‐impacts relationship is rarely defined. Both the mathematical form of this relationship (e.g., linear, exponential, and threshold) and the attributes of the invading population (e.g., density, biomass, and body size) that most efficiently describe its impacts could vary greatly across invaders, ecosystems, and ecological variables. Knowing the shape of this relationship could improve management and help to infer mechanisms of interaction between the invader and ecosystem. We used a long‐term data set on the invasion of the Hudson River ecosystem by two species of Dreissena (the zebra mussel, Dreissena polymorpha , and the quagga mussel, Dreissena rostriformis ) to explore the shape of the population‐impacts relationship for selected ecological variables, including seston, phytoplankton, and several taxa of zooplankton. Most population‐impacts relationships appeared to follow a negative exponential form, but we also found apparent thresholds and scatterplots for some variables. Including information on the traits of Dreissena (body size and filtration rate) often substantially improved models of impacts. We found only slight evidence that the resistance of the Hudson River ecosystem to the Dreissena invasion might be increasing over time. Our results suggest important refinements to widely used conceptual models of invasive species impact, and indicate that defining the population‐effects relationship will be essential in understanding and managing the impacts of non‐native species.

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Further validation of the affective bias test for predicting antidepressant and pro-depressant risk: effects of pharmacological and social manipulations in male and female rats - Justyna K. Hinchcliffe; Sarah A. Stuart; Michael Mendl; Emma S. J. Robinson (Psychopharmacology, 2017)

The assessment of neuromuscular fatigue during 120 min of simulated soccer exercise - Stuart Goodall; Kevin Thomas; Liam David Harper; Robert Hunter; Paul Parker; Emma Stevenson; Daniel West; Mark Russell; Glyn Howatson (European Journal of Applied Physiology, 2017)

Nucleus incertus promotes cortical desynchronization and behavioral arousal - Sherie Ma; Giancarlo Allocca; Emma K. E. Ong-Pålsson; Caitlin E. Singleton; David Hawkes; Stuart J. McDougall; Spencer J. Williams; Ross A. D. Bathgate; Andrew L. Gundlach (Brain Structure and Function, 2017)

Effects of sertraline, duloxetine, vortioxetine, and idazoxan in the rat affective bias test - Louise K. Refsgaard; Kia Haubro; Darryl S. Pickering; Sarah A. Stuart; Emma S. J. Robinson; Jesper T. Andreasen (Psychopharmacology, 2016)

A population approach to characterise amisulpride pharmacokinetics in older people and Alzheimer’s disease - Suzanne Reeves; Julie Bertrand; Fabrizia D’Antonio; Emma McLachlan; Akshay Nair; Stuart Brownings; Suki Greaves; Alan Smith; David Taylor; Robert Howard (Psychopharmacology, 2016)

BRCA1/2 mutation analysis in male breast cancer families from North West England - D. G. R. Evans; Mike Bulman; Karen Young; Emma Howard; Stuart Bayliss; Andrew Wallace; Fiona Lalloo (Familial Cancer, 2008)

Molecular distinction between true centric fission and pericentric duplication-fission - Jo Perry; Sara Nouri; Phung La; Art Daniel; Zhanhe Wu; Stuart Purvis-Smith; Emma Northrop; K. H. Andy Choo; Howard R. Slater (Human Genetics, 2005)